SAFETY OF THERAPY AND PATRONAGE SYSTEM IN PATIENTS WHO RECEIVE WARFARIN - E. S. Kropacheva (Атеротромбоз)
The paper discusses the most common questions regarding the safety of therapy and patronage system in patients who receive warfarin in the question and answer form. Vitamin K antagonists now are the oral anticoagulants that are most commonly used in the actual clinical practice. Despite a large accumulated body of clinical experience, it is not always easy for a doctor to pick the individual dose of warfarin.